Worry about your next job interview Here’s what hiring managers have to say - Wan Noor Farah, Wan Shamsuddin; Farah Liyana, Ahmad A'azmey; Alia Najaa, Md Nor (UMPSA, 2024)
A job interview is often perceived as a nerve-inducing social situation in which anyone wants to excel. With that, there has been a shift in tertiary education's English curriculum and syllabus in the past few years to accommodate this social situation.